Fiscal Policy in the Eurozone: Stimulus or Consolidation? - Allsopp, C (2005)
Fiscal policy is one of the three pillars of what Dr. Ottmar Issing (2002) has called the Maastricht Assignment. For the Eurozone as a whole, the Central Bank is responsible for area-wide price stability. The twelve national fiscal authorities are responsible for fiscal policy--country by country--subject to the provisions of the Stability and Growth Pact (SGP). The third pillar involves supply-side issues and wage/price developments and is the responsibility of "national governments and the social partners". Issing has argued that this assignment provides a clear division of roles and responsibilities--and that no further macroeconomic coordination is necessary or desirable. In this article, Christopher Allsopp assesses the framework for fiscal policy in the Eurozone, arguing for a system that is more decentralised; ensures 'sustainability' as a primary objective; and, subject to that, allows for activist stabilisation policy against country-specific shocks.